Model Pembelajaran Discovery Learning Berbantuan Audio Visual terhadap Kemampuan Pemahaman Pendidikan Agama Hindu dan Budi Pekerti Kelas VIII SMP Harapan Nusantara - Eka Cahayani, Ni Luh Putu; Wisnu Wardani, Dewi Ayu (Jayapangus Press, 2022)
This study aims to determine the improvement of students' understanding and achievement in Hinduism learning subjects at Harapan Nusantara Junior High School through the audio-visual assisted Idiscovery Learning model. The population of this study were all students of class VIII of Harapan Nusantara Junior High School. In this study the authors took a class that would be used as a sample, namely class VIII 1 as an experimental sample and class VIII B as a control class. This research uses quantitative research methods with experimental research types. This research procedure consists of preparation and implementation. The data collection technique used as a test, a trial test was conducted to determine the validity and reliability of the research instrument. The requirements test includes normality and homogeneity tests, data analysis in this study using the F test. The results showed that the Discovery Learning model can improve students' understanding and achievement in Hinduism learning subjects at Harapan Nusantara Junior High School. This can be proven from the test results which show that Pre-cycle there were 47% (18 children) of students who completed the KKM. In cycle 1 there were 61% (23 children) of students who completed the KKM so that the cycle was continued to achieve the desired thing. Then in cycle 2 there were also 82% (31 children) of students who had completed the KKM, so the cycle was stopped because it had achieved what was expected even though not all were declared to have passed or there were still some students who had scores below the KKM or standard (KKM). It can be concluded that this significant difference supports and shows an increase in the understanding and achievement of students in Hinduism learning subjects at Harapan Nusantara Junior High School.